Tegumento de Bombyx mori (Lepidoptera: Bombycidae) infectado pelo Bombyx mori nucleopolyhedrovirus - Oro, Alana Lucio (2017)
Bombyx mori L. (Lepidoptera: Bombycidae) is a holometabolous insect of great importance for the scientific and economic field, currently its being found only in germplasm banks. The most promising matrices are selected by characteristics of productivity and diseases resistance. The silk productive chain can be affected by several factors, and the viral diseases are responsible for considerable losses. Between the pathogens affecting silkworm, Bombyx mori nucleopolyhedrovirus (BmNPV) is a highly pathogenic virus from Baculoviridae family and Alphabaculovirus (AlphaBV) genus, which infects insects at the larval stage. BmNPV is poliorganotrophic and series of tissues are known as targets, appearing the main signs of the disease by changes in the integument. However, literature does not present information regarding cuticle disorganization during BmNPV infection, thus justifying this study. Currently, B. mori is a model organism in scientific research due to its characteristics of easy handling and rearing. There are several studies involving silkworms, usually on the genetic basis, analyzing the intrinsic qualitative and quantitative attributes of each strain. These analyses occur to select the best representatives for breeding and hybrid programs. Despite this, there are many genotypes with no information available, which limits their use in the production of pure breeds and hybrids. These information are used to improve the quality and productivity of silk, besides increase resistance to diseases, especially those caused by BmNPV. Therefore, the second study evaluated the biological and productive characteristics of two B. mori strains (BBJ and AS31) belonging to the Germplasm Bank of the State University of Maringá, Paraná, Brazil and a commercial hybrid, inoculated by BmNPV. For this purpose, B. mori hybrid caterpillars were inoculated in the 5th instar with a viral concentration 1.70x107 polyhedral occlusion bodies/ mL of BmNPV. The integument was collected on the 7th day after inoculation and followed the steps for transmission electron microscopy. The caterpillars for the genotype production characteristics analysis (BBJ, AS31 and commercial hybrid) were inoculated by eight different concentrations of BmNPV in the 5th instar. Viral infection was followed until cocoon formation, and data collected of the productive variables were analyzed statistically. The integument results revealed ultrastructure and characteristics of the BmNPV infection. These results elucidate the disruption mechanism of the microvilli plaques and the endocuticle lamellae, causing cuticle disorganization and rupture of the integument. At genotype analysis, the results indicate AS31 strain proved to be the most promising for breeding programs, which evaluated the productive traits, raw silk percent and larval cycle duration in larvae inoculated by BmNPV.